The vascular smooth muscle cell : molecular and biological responses to the extracellular matrix - Schwartz, Stephen M.; Mecham, Robert P.; ScienceDirect eBooks (San Diego : Academic Press, 1995)
In the last several years, the development of reagents that recognize smooth muscle-specific proteins has enabled researchers to identify smooth muscle cells (SMC) in tissue undergoing both differentiation and repair. These developments have led to increased research on SMC. The latest volume in the Biology of the Extracellular Matrix Series takes a current and all-encompassing look at this growing area of research. Devoted entirely to the subject of SMC, the book covers a diversity of topics-from SMC architecture and contractility to differentiation and gene expression in development. It also examines the proliferation and replication of SMC and its role in pharmacology and vascular disease. A must for cell, developmental, and molecular biologists, this book also will appeal to cardiologists, pathologists, and biomedical researchers interested in smooth muscle cells. Key Features * Presents a molecular, genetic, and developmental perspective of the vas smooth muscle cell * Overview sections highlight key points of chapters, including the clinical relevance of the research and expectations for future study * Appeals to both the basic biologist and to the biomedical researcher of vascular disease.
G.R. Campbell and J.H. Campbell, Development of the Vessel Wall: Overview. -- A.C. Gittenberger-De Groot, J. Slomp, M.C. Deruiter, and R.E. Poelmann, Smooth Muscle Cell Differentiation during Early Development and during Intimal Thickening Formation in the Ductus Arteriosus. -- M.A. Glukhova and V.E. Koteliansky, Integrins, Cytoskeletal and Extracellular Matrix Proteins in Developing Smooth Muscle Cells of Human Aorta. -- S.M. Schwartz, E.R. O'Brien, D. deBlois, and C.M. Giachelli, Relevance of Smooth Muscle Replication and Development to Vascular Disease. -- G. Liau and D.K.M. Han, Smooth Muscle Gene Expression during Developmental Maturation. -- G.K. Owens, Molecular Identifcation Smooth Muscle Cells: Overview. -- J. Victor Small and A.J. North, Architecture of the Smooth Muscle Cell. -- M. Periasamy and R. Nagai, Molecular Basis of Smooth Muscle Contractility: Myosin Heavy Chains: Gene Structure and Expression. -- T.C. McQuinn and R.J. Schwartz, Vascular Smooth Muscle-Specific Gene Expression. -- R. Ross, Molecular Controls of Smooth Muscle Hypertrophy and Hyperplasia: Overview. -- A.W. Clowes, Smooth Muscle Cell Function from the Clinical Perspective: Overview. -- M.A. Riedy, Regulation of Arterial Smooth Muscle Growth. -- C.L. Jackson, Pharmacology of Smooth Muscle Cell Proliferation. -- A. Desmouliere and G. Gabbiani, Smooth Muscle Cell and Fibroblast Biological and Functional Features: Similarities and Differences. -- J.G.R. DeMey, Smooth Muscle Cell Proliferation in Hypertension: Possible Contribution to Arterial Remodeling. -- Chapter References. -- Subject Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Vascular smooth muscle; Extracellular matrix; Muscle, Smooth, Vascular -- physiology; Muscle, Smooth, Vascular -- cytology; Extracellular Matrix -- physiology; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Extracellular matrix; Vascular smooth muscle; Bloedvaten; Gladde spieren; Extracellulaire matrix; Cells -- Structure; Electronic books